Turkey in the Black Sea region: Ankara's reactions to the war in Ukraine against the background of regional dynamics and global confrontation - Daria Isachenko (Stiftung Wissenschaft und Politik (SWP), 2023)
Turkey's policy in the Black Sea region is the result of not only a complex relationship with Russia but also of a difficult relationship with the West. In particular, US policy in the Middle East has a major impact on how Ankara positions itself in the Black Sea region. An important feature of the Black Sea region has been and continues to be the shared Turkish and Russian vision of a regional order that excludes external actors. This can be seen in the way Turkey interpreted the Montreux Convention after the outbreak of war in Ukraine and in the way the Black Sea Grain Initiative came about. Under the Montreux Convention, Ankara has a decisive role in the limitation of extra-regional fleets in the Black Sea. This is partly due to Turkish control of the straits. On the other hand, there are also treaty-based tonnage restrictions for warships of non-littoral states that are allowed to stay in the Black Sea temporarily. Ankara's manoeuvres are contributing significantly to the West's uncertainty about Turkey's foreign policy orientation. However, Ankara is not questioning its security anchorage in NATO. As well as securing its leadership role in the Black Sea region, Ankara is also keen to assert its economic interests.
Keywords: 320; War in Ukraine; Turkey; Black Sea Region; Turkey's relationship with Russia; Turkey's relationship with the West; regional order; Montreux Convention; Black Sea Grain Initiative; NATO